La météorologie appliquée à la lutte contre les incendies de forêt - Silvia Bruzzone (Revue d'anthropologie des connaissances)
The article examines how meteorological forecasts reconfigure the organization of risk management with the particular case of wild forest fire fighting. To what extent are forecasts “useful” and “adapted” to foresters’ operational work? What is the role of forecasting tools in the definition of the different strategies of wild forest fire fighting? By applying STS methods, the analysis shows how foresting takes shape through processes of “misalignment” between scientific knowledge, foresters’ operational requirements and their intent to keep control over the forecast instrument and over the definition of actions against wild forest fires. I show that forecasting takes shape through the reconfiguration of local competences in the “governance of knowledge” related to wild forest fire fighting. The critical question in applied meteorology is whether the conditions exist to challenge the established knowledge and power relations within the work practices of risk management.